2013
DOI: 10.1128/jcm.01418-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perirectal versus Rectal Swabs for Detection of Asymptomatic Carriers of Toxigenic Clostridium difficile

Abstract: bFor long-term care and spinal cord injury patients, the sensitivity, specificity, and positive and negative predictive values of perirectal versus rectal cultures for detection of asymptomatic carriers of Clostridium difficile were 95%, 100%, 100%, and 97%, respectively. Perirectal cultures provide an accurate method to detect asymptomatic carriers of C. difficile. Clostridium difficile is the most important cause of health careassociated infectious diarrhea. Asymptomatic carriage of toxigenic C. difficile is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
0
17
1
1
Order By: Relevance
“…Davies et al studied the performance of the same GDH ELFA in diarrheal samples submitted for C. difficile testing and reported a higher sensitivity of 95.8% and a similar specificity of 91% (40). The lower sensitivity found in our study could be due to presence of lower numbers of C. difficile in fecal samples of asymptomatically colonized patients than in patients with CDI (18). However, we do not exclude the possibility that the percentages change when larger number of fecal samples are tested.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Davies et al studied the performance of the same GDH ELFA in diarrheal samples submitted for C. difficile testing and reported a higher sensitivity of 95.8% and a similar specificity of 91% (40). The lower sensitivity found in our study could be due to presence of lower numbers of C. difficile in fecal samples of asymptomatically colonized patients than in patients with CDI (18). However, we do not exclude the possibility that the percentages change when larger number of fecal samples are tested.…”
Section: Discussioncontrasting
confidence: 55%
“…The studies in asymptomatically colonized patients vary greatly in patient inclusion criteria, tested material, and applied diagnostic and gold standard tests. For instance, a great number of the studies only test rectal swabs or use a combination of stool samples and rectal swabs (4,8,18,22,23,31,34). Guerrero et al showed that asymptomatic carriers have lower numbers of C. difficile in their rectal swab than CDI patients, indicating that stool samples should be preferred (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, an exception has to be made for patients suspected of CDI who have ileus. In these patients, a rectal swab can be used with adequate sensitivity and specificity for (toxigenic) culture, NAAT or GDH EIA [89,90]. The use of perirectal swabs for NAAT or GDH EIA testing might also be an alternative in selected patient populations but may depend on the presence of faecal staining of the swab [89e91].…”
Section: Discussionmentioning
confidence: 99%
“…Voraussetzung für eine rationale Diagnostik ist der Einschluss von ausschließlich ungeformten Stuhlproben [18,101]; Ausnahme sind Patienten mit Darmparalyse aufgrund eines toxischen Megakolons, bei denen die Diagnostik auch aus Rektalabstrichen mit ähnlich hoher Sensitivität möglich ist [102,103]. Wiederholungstests werden auf Grund der Studienlage generell nicht empfohlen.…”
Section: Risikofaktoren Für Erkrankung Und Rezidivunclassified